RISK ATTITUDES, MENTAL ACCOUNTING AND OVERCONFIDENCE IN INVESTMENT PLACEMENT DECISION DURING AND POST COVID-19 - Arini Novandalina; Fidyah Yuli Ernawati; Andhy Tri Adriyanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The Small and Medium Enterprises is the main pillar the people's economy. SME investment decisions related to how entrepreneurs place their funds is a very determining factor in company performance. The purpose of this study is to analyze and explain: 1) The influence of risk attitudes on company performance through decisions on the placement of working capital funds for small and medium enterprises (SMEs), 2) The effect of risk attitudes on company performance in SMEs 3) the effect of working capital fund placement decisions on the performance of SMEs. The study population was all garment, weaving, carving and batik SMEs in Jepara. The sampling technique is non-probability sampling, using assessment sampling. This study found that overconfidence behavior and risk attitude have a significant influence on investment decision making. Mental accounting doesn’t have a significant influence on investment decision making. The more investors are willing to face risks and the higher the overconfidence will increase investment decisions. The number of investors who are risk seekers in the capital market is a natural thing because stock investment is included in the high-risk investment category. Mental accounting can not influence the investment decision making.